The runaway hug - Bland, Nick, 1973-; Blackwood, Freya (New York : Random House, 2013)
Lucy borrows her mother's very last hug and shares it with each member of her family, getting it back each time until her dog, Annie, runs away with it.
Keywords: Family life -- Fiction; Hugging -- Fiction